The Influence Of Academic Supervision Of School Principals and Professional Competence Of Teachers On The Quality Of Learning in South Pemulutan Elementary School - Fashihah Fashihah; Muhammad Kristiawan; Pahlawan Pahlawan (International Journal of Studies in International Education, 2025)
This study aims to analyze the influence of the principal's academic supervision and teachers' professional competence on the quality of learning at South Pemulutan Elementary School. This study uses a quantitative method with a correlational approach. Data was obtained through questionnaires distributed to teachers, as well as observations and interviews to deepen the analysis. The results of the study show that the academic supervision of school principals has a positive and significant influence on the quality of learning. In addition, the professional competence of teachers also contributes significantly to improving the quality of learning. These findings confirm that the role of school principals in conducting academic supervision and improving teacher competence is a key factor in improving the quality of learning in elementary schools. Therefore, strengthening academic supervision and improving teacher competence need to be the main focus in education policies to improve the quality of learning.